The effectiveness of Stasiun Lambuang as a Public Space for Empowering Micro, Small, and Medium Enterprises (MSMEs) in Bukittinggi City: Efektivitas Ruang Publik Stasiun Lambuang untuk Usaha Mikro, Kecil dan Menengah (UMKM) di Kota Bukittinggi - Syafilla Dwi Pratiwi; Rahmadani Yusran (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The purpose of this research is to assess how well Stasiun Lambuang serves as a public area for empowering Bukittinggi City's MSMEs. Data was gathered by document analysis, in-depth interviews, and observation using a descriptive qualitative methodology. The results show that, as seen by ineffective zoning and passive visitor behavior, the area does not adequately address the financial demands of MSME actors. Zone 1 is less attractive due to limited facilities, while Zone 2 is more crowded due to entertainment features. Moreover, poor external visibility caused by a concrete fence reduces spontaneous visits. The analysis refers to Carr’s (1992) framework of an ideal public space, which requires responsive, democratic, and meaningful qualities. This study recommends facility revitalization, zoning rearrangement, and a more participatory management strategy.